SCIENTIFIC FUNDAMENTALS OF FINANCIAL SECURITY OF HOUSEHOLDS (Economic journal of Lesya Ukrainka Volyn National University, 2022)
The article summarizes scientific approaches to the definition of financial security of households and clarifies the place and role of financial security of households in the financial security of the state and the world. Based on the systematization of scientists' approaches to the formulation of the essence of financial security of households, it is established that the financial security of households in the hierarchical structure refers to the microeconomic level. In the hierarchical structure of financial security, in addition to the microeconomic level, it is also recommended to introduce such levels as: nanoscale, mesolevel, macroeconomic level, global level. In particular, the financial security of an individual citizen is included in the nanolevel; the microeconomic level includes financial security of enterprises and financial security of households; it is proposed to introduce financial security of the region, financial security of territorial communities and financial security of the industry to the mesoeconomic level; at the macroeconomic level, the financial security of the state is singled out, and at the global level, global financial security is included. It is substantiated that the financial security of households should be related to the microeconomic level in the hierarchical system of financial security.It is proposed to classify the current approaches to determining the essence of financial security of households in two directions: resource-functional and strategic-target. It is substantiated that in accordance with the resource-functional approach, the financial security of households is considered in terms of adequacy of formation and efficiency of use of financial resources of households to ensure the implementation of their functions. It is noted that the strategic-targeted approach to the interpretation of the concept of financial security of households takes into account, first of all, the functions that financial security must perform in order to form opportunities for household development in future periods.Based on a critical analysis of scholars' views on understanding the essence of the concept of "financial security of households", the author's approach to the interpretation of this concept taking into account the resource-functional approach. We believe that financial security of households is a system of financial, economic, social and legal relations that ensures the most efficient formation and use of financial resources of households to determine the mechanism for identifying and mitigating the negative impact of external and internal threats and maximizing household welfare.
Keywords: financial security, households, hierarchical structure, microeconomic level, resource-functional approach, strategic-target approach